Surviving the slowdown - Begg, David; Centre for Economic Policy Research (Great Britain) (London : Centre for Economic Policy Research, 2002)
This series brings together a group of economists known for their work on macroeconomics and montetary policy. It is intended to monitor the European economy and the work of the ECB. A MECB report is published each year, complemented by an update that draws on contemporary publications of the ECB.
Includes bibliographical references.
oif 27/02/15
Loan
Keywords: European Central Bank; Monetary policy -- European Union countries; Banks and banking, Central -- European Union countries